Analisis Penerapan Akuntansi Aset Tetap Berdasarkan PSAK No. 16 pada PT Kaltim Kariangau Terminal - Nuraini Wahyu Aprilia; Jantje Tinangon; Sherly Pinatik (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
Fixed assets are tangible assets that are obtained in ready to use form or by being built first, which are used in the company's operations, are not intended for sale in the context of the company's normal activities and have a useful life of more than one year. Fixed assets are an important part in supporting the company's operational activities. This study aims to determine that the company has implemented fixed asset accounting that is appropriate and based on the Statement of Financial Accounting Standards (PSAK) No.16 in the company's activities. The type of research used is qualitative research with descriptive methods. The results showed that the application of fixed asset accounting applied by the company in general is in accordance with PSAK No. 16. While some things related to the application of fixed asset disclosures and related to the application of termination and disposal of fixed assets are not in accordance with PSAK No. 16.